2021
DOI: 10.1016/j.adro.2020.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Ablative Five-Fraction Stereotactic Body Radiation Therapy for Inoperable Pancreatic Cancer Using Online MR-Guided Adaptation

Abstract: Purpose Patients with inoperable pancreatic adenocarcinoma have limited options, with traditional chemoradiation providing modest clinical benefit and an otherwise poor prognosis. Stereotactic body radiation therapy for pancreatic cancer is limited by proximity to organs-at-risk (OAR). However, stereotactic magnetic resonance-guided adaptive radiation therapy (SMART) has shown promise in delivering ablative doses safely. We sought to demonstrate the benefits of SMART using a 5-fraction approach wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
97
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 25 publications
5
97
1
1
Order By: Relevance
“…MRgRT is a novel technique that facilitates dose escalation in the abdomen beyond what has been historically feasible using CT. 5,17,22,38 SMART delivered with Co-60 was tolerated remarkably well in an analysis by Rudra et al of 44 pancreas patients, with 25 receiving dose escalation to 40 to 67.5 Gy over 5 to 15 fractions. 5 The minority received 5 fractions although it was not specified how many received at least 50 Gy (BED 10 100 Gy 10 ); it was likely a small number given the median prescribed BED 10 was 77.6 Gy 10 .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…MRgRT is a novel technique that facilitates dose escalation in the abdomen beyond what has been historically feasible using CT. 5,17,22,38 SMART delivered with Co-60 was tolerated remarkably well in an analysis by Rudra et al of 44 pancreas patients, with 25 receiving dose escalation to 40 to 67.5 Gy over 5 to 15 fractions. 5 The minority received 5 fractions although it was not specified how many received at least 50 Gy (BED 10 100 Gy 10 ); it was likely a small number given the median prescribed BED 10 was 77.6 Gy 10 .…”
Section: Discussionmentioning
confidence: 98%
“…There has recently become greater enthusiasm in radiation dose escalation for inoperable pancreas cancer to potentially improve clinical outcomes. 4e8, 10,17 Investigators from MD Anderson Cancer Center reported that LAPC patients, typically treated in 28 fractions with daily CT guidance, had higher median survival (17.8 vs 15.0 months; P Z .03) and local-regional relapse free survival (10.2 vs 6.2 months; P Z .05) when a biologically effective dose (BED 10 ) >70 Gy 10 was prescribed (Table 4). 4 Dose intensification was considered, typically with fractionation over multiple weeks to mitigate toxicity, if there was !1 cm between tumor and luminal GI structures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations